Penggunaan Media Strip Story dalam Meningkatkan Maharah Kitabah Mahasiswi Intensif Idia - Dewi Nurhayati; Nuria Usman (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
The use of strip story media is one of a series of stories that are cut into each word and the word is pasted onto cardboard or read by female students, this media can be used to practice writing Arabic or arrange words into sentence arrangements and so on, such as imla' khat and insya, especially in learning inysa (kitabah). The problem being studied is to find out how the use of strip story media is carried out by Intensive Semester III B students in writing maharah kitabah and whether there is an improvement in the Arabic writing ability of intensive students in semester III B. This research uses descriptive qualitative research. The informants selected in this study are the names involved in using this media. Like the Ustadzah and their students, the location of the research was carried out at the Al-Amien Prenduan Islamic boarding school, especially in Idia (intensive). Data collection techniques include interviews, observation and doccutation, while data analysis techniques include data reduction, data presentation. The result of the study is that the use of strip story media for maharah kitabah greatly adds to the improvement of writing practice into neat and good Arabic. So it is said to be good and neat if it has gone through the steps of the provisions that have been listed.